The Effect Of Worship Facilities, Halal Food And Islamic Morality On The Decisions Of Muslim Tourists Visiting The Tourism Village Of Kampoeng Lama Paloh Naga, Pantai Labu District, Deli Serdang Regency - Masditou Adit (Politeknik Pariwisata Medan, 2022)
Worship Facilities, Halal Food and Drinks and Islamic Morality together contribute to each other in linking the system to achieve / meet the needs of tourists so that this will be significant to Muslim Tourist Decisions. The prospects in this area are potential areas and strategies to be managed and developed in supporting the momentum of halal tourism. In this case, to realize halal tourism facilities, there are several supporting indicators, namely worship, halal food and drinks, and Islamic morality. With this strategic area and great potential, making the Kampoeng Lama Paloh Naga Tourism Village to develop in seeing the tourism sector that has Islamic values ​​or better known as halal tourism. Quantitative derivation method is used as an analytical technique in this case study. Where the correlation hypothesis testing and regression analysis between variables will be carried out using an error rate approach of 5% and a confidence level of 95%. The data collected in the form of numbers are then parsed and researched in order to get some information that interprets these numbers. Each variable operates separately from the dependent variable. The findings of this study. Facilities and halal food and beverages have a positive and significant effect on the decisions of Muslim tourists by 56.70% in the tourist village of Kampoeng Lama Paloh Naga, Pantai Labu District, Deli Serdang Regency.